Analisis Kesulitan Guru di Sekolah Dasar dalam Menyusun Modul Ajar Kurikulum Merdeka - Amelia, Erlina (BASICA, 2023)
The discussion of the problem in this research is that the teaching module is not planned well. This teaching module that is not planned well is usually due to teacher confusion when creating the teaching module. Therefore, in this research, research was conducted that only focused on teachers' difficulties in compiling teaching modules in elementary schools. The type of research used in this research is qualitative descriptive research. This research was carried out at three elementary schools in Majalengka Regency which used the Merdeka Curriculum. The data source used in this research was from interviews with 6 teachers who taught at three elementary schools in Majalengka Regency. The instruments in this research used an interview guide grid and an interview sheet. Based on the identification from the results of the interviews that had been conducted, there were several difficulties experienced by teachers in compiling the Independent Curriculum teaching modules. Most teachers already know the criteria for a good teaching module. However, there are several difficulties experienced by these teachers, including difficulties in determining learning outcomes, determining learning objectives, determining learning models, creating learning steps, determining media, finding appropriate references, or in making assessments.